Chadwick F. Alger Pioneer in the Study of the Political Process and on NGO Participation in the United Nations - Alger, Chadwick F. (SpringerBriefs on Pioneers in Science and Practice, 2014)
This volume honors the lifetime achievements of distinguished scholar Chadwick F. Alger on the occasion of his 90th birthday. Carolyn Stephenson presents Prof. Alger as a Pioneer in the Study of the Political Process and on NGO Participation in the United Nations. Part 1 offers an autobiographical note and a comprehensive bibliography of his academic publications. Part II includes three texts on "The Political Process in the UN," namely "The Researcher in the United Nations: Evolution of a Research Strategy," "Interaction in a Committee of the United Nations General Assembly" and "Interaction and Negotiation in a Committee of the UN GA."  In Part III, which focuses on "Civil Society Organizations in the UN System (NGOs)," three chapters deal with "Evolving Roles of NGOs in Member State Decision-making in the UN System," "The Roles of NGOs in the UN System: From Article 71 to a People's Millennium Assembly" and "Strengthening relations between NGOs and the UN system: Towards a research agenda.".